Return to play and performance after anterior cruciate ligament reconstruction in soccer players: a systematic review of recent evidence - Manojlovic, M.; Ninkovic, S.; Matic, R.; Versic, S.; Modric, T.; Sekulic, D.; Drid, P. (Sports Medicine, 2024)
Background: The available literature referring to the return to play (RTP) and performance after anterior cruciate ligament reconstruction (ACLR) has already been comprehensively summarized in team sports such as basketball or American Football. Therefore, in this sense, it is necessary to synthesize evidence relating to the mentioned parameters in soccer players who underwent ACLR. Objective: The aim of this systematic review was to examine RTP and the performance of soccer players after ACLR. Methods: Three electronic databases, Web of Science, Scopus, and PubMed, have been comprehensively searched to identify relevant articles. The following inclusion criteria were applied: (1) the sample of respondents consisted of soccer players irrespective of their age, sex, or level of competition; (2) athletes experienced anterior cruciate ligament injury and underwent ACLR; (3) outcomes estimated referred to the RTP, RTP at the preinjury level of competition, RTP time, performance, and career duration of soccer players; (4) studies were written in the English language. The methodological quality of the research was evaluated using the Methodological Index for Non-Randomized Studies (MINORS). Results: Databases searched yielded a total of 694 studies, of which 17 fulfilled the eligibility criteria and were included in the final analysis. These included 3657 soccer players, 2845 males and 812 females, who underwent ACLR and most commonly competed at the elite, national, amateur, and recreational levels. The results obtained indicated that 72% of soccer players successfully RTP and 53% RTP at the preinjury level of participation after ACLR. In addition, recent evidence provided in this literature review demonstrated that mean RTP time was 264 days or 8.7 months. Moreover, the majority of the studies unambiguously suggested that performance related to statistical aspects noticeably deteriorated compared with both the preinjury period and noninjured athletes. The mean career length of soccer players following ACL surgery was approximately between 4 and 5 years. Conclusion: Although a high percentage of athletes RTP after a relatively short period of absence from the sports field compared with other sports closely related to soccer, ACLR negatively impacts soccer players` performance and career duration.